2018
DOI: 10.1128/jb.00779-17
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Landscape and Regulatory Roles of Small Noncoding RNAs in the Oxidative Stress Response of the Haloarchaeon Haloferax volcanii

Abstract: Haloarchaea in their natural environment are exposed to hypersalinity, intense solar radiation, and desiccation, all of which generate high levels of oxidative stress. Previous work has shown that haloarchaea are an order of magnitude more resistant to oxidative stress than most mesophilic organisms. Despite this resistance, the pathways haloarchaea use to respond to oxidative stress damage are similar to those of nonresistant organisms, suggesting that regulatory processes might be key to their robustness. Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(92 citation statements)
references
References 77 publications
4
88
0
Order By: Relevance
“…In the halite community, we found that asRNA expression levels were negatively correlated with those of their putative targets, with highly expressed asRNAs overlapping lowly expressed protein-encoding genes. A similar trend was reported in the haloarchaeon H. volcanii when investigating oxidative stress-responsive sRNAs, and most of the putative targets were transposase genes (21). Putative target gene func-tions in our study were mostly from haloarchaea and enriched for transport systems, cell membrane, and cell wall metabolism, with a large number of hypotheticals.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In the halite community, we found that asRNA expression levels were negatively correlated with those of their putative targets, with highly expressed asRNAs overlapping lowly expressed protein-encoding genes. A similar trend was reported in the haloarchaeon H. volcanii when investigating oxidative stress-responsive sRNAs, and most of the putative targets were transposase genes (21). Putative target gene func-tions in our study were mostly from haloarchaea and enriched for transport systems, cell membrane, and cell wall metabolism, with a large number of hypotheticals.…”
Section: Discussionsupporting
confidence: 84%
“…SnapT for sRNA community identification. An analytic pipeline, SnapT for Small ncRNA Annotation Pipeline for (meta)Transcriptomic data, was adapted from our previous work (21) to find, annotate, and quantify intergenic and antisense sRNA transcripts from transcriptomic or metatranscriptomic data. In brief, de novo transcripts were assembled from RNA reads mapped to the metagenomic assembly, and transcripts that could not be explained by any protein-coding region and did not encode peptides were extracted and further validated as sRNAs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a read count-based differential expression analysis to identify differentially 133 expressed sRNA and mRNA transcripts. The program featureCounts (Liao,Smyth,and 134 Shi 2014) was used to rapidly count reads that map to the assembled RNA transcripts 135 (described above) as previously described (Gelsinger and DiRuggiero 2018a). In order 136 to account for organism abundance changes (as opposed to true transcript changes), 137…”
Section: Metatranscriptomic Correlation and Differential Expression Amentioning
confidence: 99%